2012
DOI: 10.1177/0278364912452675
|View full text |Cite
|
Sign up to set email alerts
|

Distributed robotic sensor networks: An information-theoretic approach

Abstract: In this paper we present an information-theoretic approach to distributively control multiple robots equipped with sensors to infer the state of an environment. The robots iteratively estimate the environment state using a sequential Bayesian filter, while continuously moving along the gradient of mutual information to maximize the informativeness of the observations provided by their sensors. The gradient-based controller is proven to be convergent between observations and, in its most general form, locally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 34 publications
0
100
0
3
Order By: Relevance
“…Instead, the goal is often to maximize some measure of coverage or information [180], [181]. The robots in the team communicate over a multi-hop network and solve the surveillance task in a distributed fashion.…”
Section: Robot Capabilities Rmentioning
confidence: 99%
“…Instead, the goal is often to maximize some measure of coverage or information [180], [181]. The robots in the team communicate over a multi-hop network and solve the surveillance task in a distributed fashion.…”
Section: Robot Capabilities Rmentioning
confidence: 99%
“…Assuming that the field under measure can be modeled as a Gaussian process (GP), researchers have proposed multiple criteria for predicting the "informativeness" of a sampling position, most commonly either the variance of the GP or mutual information. Mutual information has been shown to be a more effective measure of sample utility [2], and has subsequently been used for both sensor placement [3] and the control of mobile sensors [4], [5], [6]. Alternative methods have been proposed to better cope with a lack a priori information about the field under measure.…”
Section: Related Workmentioning
confidence: 99%
“…In their paper, the authors recommended the use of uncertainty in the absence of such true data. For a multi-robot case, Julian et al (2012) suggested an exploration strategy using MI. Their work solves for an optimal SLAM control strategy by evaluating the gradient of MI.…”
Section: Active Slammentioning
confidence: 99%